Plain speaking - Sattanathan, A.N. (Delhi, 2007)
In a complementary narrative, Sattanathan's lectures-on 'The rise and spread of the non-Bhramin movement' as the most outstanding event in South Indian history in the twentieth century-offer a lucid summary of the cultural and historical conditions that fin more personal and immediate expression in the memoirs.
Keywords: Casteism-India